2008
DOI: 10.1073/pnas.0804799105
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymorphisms at the BCL11A , HBS1L-MYB , and β- globin loci associate with fetal hemoglobin levels and pain crises in sickle cell disease

Abstract: Sickle cell disease (SCD) is a debilitating monogenic blood disorder with a highly variable phenotype characterized by severe pain crises, acute clinical events, and early mortality. Interindividual variation in fetal hemoglobin (HbF) expression is a known and potentially heritable modifier of SCD severity. High HbF levels are correlated with reduced morbidity and mortality. Here, we genotyped additional BCL11A SNPs, HBS1L-MYB SNPs, and an SNP upstream of G ␥-globin (HBG2; the XmnI polymorphism), in two indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
454
5
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 517 publications
(517 citation statements)
references
References 28 publications
33
454
5
8
Order By: Relevance
“…Besides increasing the concentration of HbF, these mechanisms confer benefits such as reduced hemolysis, decreased adhesion of erythrocytes, leukocytes, and platelets to the vascular endothelium, and vasodilatation, contributing to a reduction in vaso-occlusive and inflammatory complications (Lettre et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Besides increasing the concentration of HbF, these mechanisms confer benefits such as reduced hemolysis, decreased adhesion of erythrocytes, leukocytes, and platelets to the vascular endothelium, and vasodilatation, contributing to a reduction in vaso-occlusive and inflammatory complications (Lettre et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The SNPs evaluated in this paper showed a strong association with the HbF levels in a wide spectrum of populations, including those from Europe, North America and Brazil where three joint QTLs (rs9399137, 4895441 y rs11886868) explain more than 20% of HbF variability (5,18,22). Therefore, they are suited to estimate the prevalence of HbFpromoting alleles at these loci.…”
Section: Discussionmentioning
confidence: 99%
“…These variants occur in two subloci, HMIP-A and HMIP-2B, that map to distinct enhancer elements for MYB (3,4, Menzel, et al, manuscript in preparation). HbF-increasing alleles at all three regions loci have subsequently been shown to alleviate the severity of sickle cell anemia and beta-thalassemia (5,6). Additional QTLs have been detected on chromosomes 8 and X through linkage analysis but have not been mapped in detail (7).…”
mentioning
confidence: 99%
“…Interest in the different haplotypes is mainly to do with clinical applicability, with the central hypothesis of these studies linking the severity of clinical manifestations to the haplotype present in the patient 3 (Nagel, 1984). Although there are studies that do not corroborate this hypothesis (Fullwiley, 2011), research into the diversity of hemoglobin S haplotypes has been central in the field of genetics of hemoglobin S. There are also studies that seek to establish differentiations within haplotypes and other genetic factors in order to explain the differences in the severity of the symptoms (Lettre, 2008). As we shall see later, some of these studies have suggested that the Brazilian population could be promising for studying the genetic factors that influence the clinical manifestations of the disease due to its high degree of miscegenation (Silva et al, 2011).…”
Section: Hemoglobin S In Brazilmentioning
confidence: 99%